Proximal caries infiltration – Pragmatic RCT with 4 years of follow-up. (August 2021) - Meyer-Lueckel, H.; Wardius, A.; Krois, J.; Bitter, K.; Moser, C.; Paris, S.; Wierichs, R.J.
Abstract: Objectives: Efficacy of proximal caries infiltration to arrest lesion progression has been shown in university settings, but only once in a practice-based pragmatic design with a follow-up of 18 months. The aim of this randomized split-mouth placebo-controlled study was to follow-up this cohort for 3 years and those with high caries risk for 4 years. Methods: Originally, in 87 children and young adults pairs of 238 proximal caries lesions, radiographically extending into inner half of enamel (E2) or outer third of dentin (D1), were randomly allocated to two groups: infiltration (Icon; DMG) or mock (control) treatment by five dentists in four private practices. All subjects received risk-related instructions for diet, flossing and fluoridation. The primary outcome was radiographic lesion progression (pairwise comparison) evaluated by two evaluators independently being blinded to treatment allocation. Results: After 36 months [mean (SD): 1152 (166) days] 165 lesion pairs in 64 patients as well as after 48 months [mean (SD): 1496 (121) days] 71 lesion pairs in 20 high caries risk patients could be re-evaluated clinically as well as radiographically using individualized bitewing holders as at baseline. No adverse events could be observed. After 36 months, progression was recorded in 23/165 test (14%) and 64/165 control lesions (39%) [McNemar/Obuchowski test; p <0.001; relative risk reduction (CI95%): 64 (45–77%)]. After 48 months lesion progression was recorded in 13/71 test (18%) and 34/71 control lesions (48%) [ p  = 0.003; relative risk reduction (CI95%): 62 (34–78%)] of high caries risk patients. Conclusions: It can be concluded that also in a practice-setting proximal caries infiltration is more efficacious in reducing lesion progression compared with individualized non-invasive measures alone over a period of four years.